Transcriptional profiling of two muscadine grape cultivars “Carlos” and “Noble” to reveal new genes, gene regulatory networks, and pathways that involved in grape berry ripening - Chang, Yuru; Ahlawat, Yogesh Kumar; Gu, Tongjun; Sarkhosh, Ali; Liu, Tie (Frontiers in Plant Science, 2022)
In commercial fruit production, synchronized ripening and stable shelf life are important properties. The loosely clustered or non-bunching muscadine grape has unrealized potential as a disease resistant cash crop, but requires repeated hand harvesting due to its unsynchronized or long or heterogeneous maturation period. Genomic research can be used to identify the developmental and environmental factors that control fruit ripening and postharvest quality. This study coupled the morphological, biochemical, and genetic variations between ‘Carlos’ and ‘Noble’ muscadine grape cultivars with RNA-sequencing analysis during berry maturation. The levels of antioxidants, anthocyanins, and titratable acids varied between the two cultivars during the ripening process. We also identified new genes, pathways, and regulatory networks that modulated berry ripening in muscadine grape. These findings may help develop a large-scale database of the genetic factors of muscadine grape ripening and postharvest profiles and allow the discovery of the factors underlying the ripeness heterogeneity at harvest. These genetic resources may allow us to combine applied and basic research methods in breeding to improve table and wine grape ripening uniformity, quality, stress tolerance, and postharvest handling and storage.